PERANCANGAN BISNIS START-UP DAN PROTOTYPE BUMBU MASAK SIAP PAKAI - Andra Rizky Yuwono; Ferryanto Chia (Jurnal Vicidi, 2016)
Proposal titled "START - UP BUSINESS DESIGN AND INSTANT SPICES PROTOTYPE" contains the draft business start-ups and instant spices prototypes are intended for people who was busy with their work so they can’t spare some amount of time to cook. This business start-up draft was made because the community needed a way to shorten their cooking time. The purpose of the business design and instant spices is to create a spices that can shorten the cooking time people who have a limited amount of time. Preparation of proposals will be based on the survey.